Analysis and generalization of the experience of preparing and conducting on-line group exercises under quarantine - Zmiіvskіy, G.; Petruk, O.; Pugach, V. (New Collegium, 2020)
In connection with the transfer of the educational process of higher educational institutions of Ukraine for the period of the national quarantine to the distance learning mode, scientific and pedagogical workers have encountered certain difficulties in the effective implementation of group exercises. In order to overcome these difficulties and avoid mistakes in the future, it became necessary to study the experience of preparing and conducting teachers of this type of training using distance learning technologies and formulating relevant technological and methodological recommendations. The possibilities of existing platforms that implement distance learning technologies are considered. The results of the analysis and generalization of the experience of preparing and conducting on-line group exercises by teachers of the Military-Law Institute of the Yaroslav Mudryi National Law University in a national quarantine are presented. Ways to increase their effectiveness are proposed. Technological and methodological recommendations on the preparation and conduct of this type of distance learning are formulated. The content of the distance course developed on the basis of the Moodle platform is justified for the preparation of cadets (students) for a group exercise, the requirements for the placement of educational literature in the environment of the Moodle system. A rational methodology for preparing for the lesson is determined. The possibilities of Zoom online conference platform on the implementation of distance learning technologies in the educational process are shown. The technical requirements for the organization of the lesson are outlined. The content of the teacher’s presentation and the procedure for its demonstration are analyzed. The possibilities of attracting a second teacher to the lesson and using interactive teaching methods (key issues and working in small groups) to enhance the creative and cognitive activities of cadets (students) and also to increase the level of organization of the lesson are considered. The criteria for evaluating cadets (students) based on the results of a group exercise are determined.